Use and abuse of the quasi-steady-state approximation - Flach, E; Schnell, S (2006)
The transient kinetic behaviour of an open single enzyme, single substrate reaction is examined. The reaction follows the Van Slyke–Cullen mechanism, a spacial case of the Michaelis–Menten reaction. The analysis is performed both with and without applying the quasi-steady-state approximation. The analysis of the full system shows conditions for biochemical pathway coupling, which yield sustained oscillatory behaviour in the enzyme reaction. The reduced model does not demonstrate this behaviour. The results have important implications in the analysis of open biochemical reactions and the modelling of metabolic systems.